The little book of market myths : how to profit by avoiding the investing mistakes everyone else makes - Fisher, Kenneth L.; Hoffmans, Lara. (India : Wiley, 2013)
"Ken exposes some of the most common - and deadly - myths investors swear by, and he demonstrates why the rules-of-thumb approach to investing may be robbing you of the kinds returns you hope for"--
Bonds Are Safer Than Stocks -- Asset Allocation Shortcuts -- Volatility and Only Volatility -- More Volatile Than Ever -- The Holy Grail - Capital Preservation and Growth -- The GDP-Stock Mismatch Crash -- 10% Forever! -- High Dividends for Sure Income -- The Perma-Superiority of Small-Cap Value -- Wait Until You're Sure -- Stop-Losses Stop Losses -- High Unemployment Kills Stocks -- Over-Indebted America -- Strong Dollar, Strong Stocks -- Turmoil Troubles Stocks -- News You Can Use -- Too Good to Be True.
Includes bibliographical references.
Keywords: Investments; Investments -- Decision making; Securities; Portfolio management